PENDEKATAN FILSAFAT ISLAM DALAM PENGEMBANGAN ILMU-ILMU KEUSHULUDDINAN - Muhammad Zainal Abidin (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2015)
Ushuluddin is a fundamental root of Islamic sciences. Unfortunately, in its development, Ushuluddin as a scientificthing is considered irrelevant to answer society problems. It will be understood Ushuluddin just taught religious doctrineexclusively without communicating it to social problems now. Ushuluddin basically is built based on the spirit of faith,Islam, and ihsan through philosophical approach is expected to further enrich Ushuluddin science itself, which in turnis the Ushuluddin will be able to respond to the challenges of modernity. Ushuluddin Faculty as a specific place tolearn Ushuluddin sciences is encouraged to contribute in Islamic development, especially in Islamic thinking. Althoughthe faculty does not have a lot of students, but those who enter Ushuluddin must have excellent academic ability andexpertise of religion above the average, in addition of course good morals. After all, this writing discussed aboutIslamic philosophical approach in developing Ushuluddin sciences.